Hexagonal boron nitride ceramic and preparation method and application thereof
Patent Information
- Application Number
- CN202611044682.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-14
- Publication Date
- 2026-09-11
AI Technical Summary
此外硅橡胶复合绝缘子的伞裙由有机硅橡胶材料制成,复合绝缘子在运行中会发生粉化现象,粉化层厚度分布不均匀,去除粉化层后伞裙样品憎水性变差、粗糙度降低、介电性能下降,在湿热环境下,硅橡胶表面微观形貌逐渐劣化,出现孔洞等缺陷
本发明通过对六方氮化硼块体表面喷涂改性涂层实现高疏水。涂层中,作为强疏水性基团的长氟碳连与长链烷基对纳米二氧化硅进行表面改性,构建微纳米级粗糙结构,搭配低表面能的聚二甲基硅氧烷,大幅减小水滴与涂层的接触面积,使水滴呈球状并滚落。应用于伞裙绝缘子伞裙后,能有效阻止液滴在伞裙表面形成连续水膜;同时,陶瓷本身的极高导热系数,可在涂层内部形成有效的导热网络,快速融化表面冰层,结合超疏水性降低冰与伞裙表面的附着力,从而实现伞裙的自清洁与抗冰覆盖,尤其适用于各种重污秽以及防火要求高的地区的输电线路。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of ceramic technology, specifically to a hexagonal boron nitride ceramic, its preparation method, and its application. Background Technology
[0002] Hexagonal boron nitride ceramics possess comprehensive characteristics such as low density, good machinability, excellent thermal shock resistance, and good thermal and chemical stability, making them promising for applications in aerospace, electronics, metallurgy, and machinery manufacturing.
[0003] However, boron nitride is a covalent compound with a high melting point, low solid-state self-diffusion coefficient, and a layered crystal structure, which inhibits sintering densification, resulting in a certain porosity in boron nitride ceramics. Furthermore, the raw material powder used to prepare boron nitride ceramics often contains hygroscopic boron oxide, which easily absorbs moisture in humid environments, affecting the dielectric constant and loss, and consequently impacting its wave transmission. Hexagonal boron nitride has a unique layered structure and a low solid-state diffusion coefficient, making it difficult to sinter and densify. Currently prepared single-phase hexagonal boron nitride ceramics still have relatively low mechanical properties, limiting their practical applications. The bulk hexagonal boron nitride ceramics widely used in industry are brittle, have low compressive strength, and can only withstand very limited elastic deformation. The high brittleness, high processing cost, and sensitivity to performance fluctuations of boron nitride composite ceramics restrict their widespread application in applications requiring high mechanical strength. When hexagonal boron nitride ceramics are used in applications such as high-voltage insulator skirts that need to withstand mechanical impacts such as ice shedding, wind vibration, and construction collisions, their relatively low mechanical properties become a key limiting factor.
[0004] Currently, besides silicone rubber composite insulators, a large number of porcelain insulator skirts in transmission lines are still made of electrical porcelain. Although electrical porcelain has good weather resistance and chemical stability, it also has significant defects in actual operation. The surface of electrical porcelain is hydrophilic, and it is prone to forming a continuous water film in humid, hazy, and polluted environments, leading to increased leakage current and a significant decrease in flashover voltage, seriously threatening the safe operation of the line. In addition, electrical porcelain is a typical brittle material with poor impact toughness. Under the mechanical stress of ice shedding, strong wind vibration, bird pecking, and construction collisions, the skirt is prone to breakage or even string failure. Therefore, there is an urgent need to develop a new type of ceramic skirt material that combines high mechanical strength, excellent hydrophobic anti-flashover performance, and corrosion resistance. Furthermore, the skirts of silicone rubber composite insulators are made of organosilicon rubber. Composite insulators will experience pulverization during operation, with uneven distribution of the pulverized layer thickness. After removing the pulverized layer, the hydrophobicity of the skirt sample deteriorates, the roughness decreases, and the dielectric properties decline. In humid and hot environments, the microstructure of the silicone rubber surface gradually deteriorates, and defects such as pores appear.
[0005] Based on this, the present invention will provide a method for preparing hexagonal boron nitride ceramics and their application in insulator skirts. Summary of the Invention
[0006] To address the shortcomings mentioned in the background art, the present invention aims to provide a hexagonal boron nitride ceramic, its preparation method, and its application. A modified coating is applied to the hexagonal boron nitride ceramic to improve its hydrophobicity, electrical insulation, mechanical properties, and corrosion resistance.
[0007] The objective of this invention can be achieved through the following technical solutions: A method for preparing hexagonal boron nitride ceramics includes the following steps: Step 1: Take 1-2μm hexagonal boron nitride powder, 200-400nm hexagonal boron nitride powder, and 200-500nm silicon carbide powder. Treat them with 5-15% dilute hydrochloric acid solution to remove impurities, and wash and dry them. Mix the powder with boron oxide and put it into a ball mill jar. Add zirconium oxide grinding balls and anhydrous ethanol, and ball mill for 20-24 hours. Then dry and sieve the ball-milled mixture. Put the obtained composite powder into a mold and sinter it in a vacuum atmosphere using a spark plasma sintering furnace. Then slowly depressurize and cool with the furnace. After the instrument cools to room temperature, take out the sample to obtain hexagonal boron nitride ceramic block. Step 2: Take polydimethylsiloxane and 200-400nm hexagonal boron nitride powder, add them to a mixed solution of n-hexane and ethanol, sonicate the mixed solution for 10-20 minutes, then add modified nano-silica to the mixed solution, sonicate for 20-30 minutes to obtain a modified coating, spray the modified coating onto the cleaned hexagonal boron nitride ceramic block, dry at room temperature for 20-30 minutes after spraying, and then place it in an oven at 100-120℃ to dry for 2-3 hours to obtain hexagonal boron nitride ceramic.
[0008] More preferably, in the first step, the mass ratio of 1-2μm hexagonal boron nitride powder, 200-400nm hexagonal boron nitride powder, 200-500nm silicon carbide powder, and boron oxide is 60-66:25-29:5-15:5-6.
[0009] More preferably, the sintering temperature in the first step is 1500-1700℃, the sintering pressure is 40-50MPa, and the holding time is 10-15min.
[0010] More preferably, in the second step, the mass ratio of polydimethylsiloxane, 200-400nm hexagonal boron nitride powder, and modified nano-silica is 3-5:0.4-0.8:1.6-2.4.
[0011] More preferably, the volume ratio of hexane to ethanol in the mixed solution of hexane and ethanol is 1:2.
[0012] More preferably, the method for preparing modified nano-silica includes the following steps: After activating nano-silica at 350-400℃ for 5-7h, it is added to the reactor along with a modifier and toluene. The mixture is then ultrasonically dispersed at room temperature for 15-25min. The system temperature is then raised to 70-80℃ and reacted at this temperature for 8-12h. After the reaction is complete, the solid is filtered out, washed with anhydrous ethanol, and dried to obtain modified nano-silica.
[0013] More preferably, the mass ratio of nano-silica to modifier is 2-3:1-1.2.
[0014] More preferably, the method for preparing the modifier includes the following steps: S1. Vanillin and 3-pentadecanylphenol were placed in a reactor, and anhydrous ethanol was added. A mixture of concentrated sulfuric acid and anhydrous ethanol was added dropwise under an ice-water bath. After the addition was complete, the temperature was raised to 25-30℃ and the reaction was stirred for 1-3 hours. After the reaction was completed, the product was extracted with ethyl acetate and the organic phase was retained. The organic phase was then washed with saturated brine and dried to obtain a hydrophobic intermediate. S2. Take the hydrophobic intermediate and cesium carbonate in a reactor, add dimethyl sulfoxide under a nitrogen atmosphere, stir the reaction at 30-35℃ for 10-14h, then raise the temperature to 40-50℃, add 2-bromo-2-perfluoro-n-butylethylene dropwise to the mixed system, and after the dropwise addition is completed, react at a constant temperature for 20-24h. After the reaction is completed, filter to remove the solid, distill the filtrate under reduced pressure, extract with ethyl acetate and retain the organic phase, wash the organic phase with saturated sodium chloride solution and deionized water respectively and dry to obtain the hydrophobic agent; S3. Take the hydrophobic agent, lithium hydroxide, and isopropanol into a reactor, add the silane coupling agent under a nitrogen atmosphere, stir the reaction at room temperature for 3-4 hours, remove the solvent by rotary evaporation after the reaction is completed, and then dry the product to obtain the modifier.
[0015] More preferably, in step S1, the mass ratio of vanillin to 3-pentadecanylphenol is 0.25-0.32:0.6-1.
[0016] More preferably, in step S1, the volume ratio of concentrated sulfuric acid to anhydrous ethanol in the mixture of concentrated sulfuric acid and anhydrous ethanol is 0.5-0.6:1-1.2, and the mass fraction of concentrated sulfuric acid is 95-98%.
[0017] More preferably, in step S2, the mass ratio of the hydrophobic intermediate, cesium carbonate, and 2-bromo-2-perfluoro-n-butylethylene is 0.5-0.7:0.9-1.1:0.9-1.1.
[0018] More preferably, the mass ratio of hydrophobic agent, lithium hydroxide, and silane coupling agent in step S3 is 0.9-1.1:0.05-0.06:0.5-0.6.
[0019] More preferably, the silane coupling agent is silane coupling agent KH-550 or silane coupling agent KH-540.
[0020] The above-mentioned application of hexagonal boron nitride ceramics in power and energy systems involves using the hexagonal boron nitride ceramics as insulator skirts for high-voltage transmission lines.
[0021] More preferably, in application, the second step of the preparation method of the hexagonal boron nitride ceramic is formed using an umbrella skirt mold, followed by subsequent spraying to obtain a hexagonal boron nitride ceramic umbrella skirt, which is then assembled with the insulator core rod and fittings by adhesive or mechanical clamping to form a complete insulator for use in transmission lines.
[0022] The beneficial effects of this invention are: This invention achieves high hydrophobicity by spraying a modified coating onto the surface of a hexagonal boron nitride bulk material. In the coating, long-chain fluorocarbons and long-chain alkyl groups, acting as strongly hydrophobic groups, modify the surface of nano-silica, constructing a micro-nano-scale rough structure. Combined with low-surface-energy polydimethylsiloxane, this significantly reduces the contact area between water droplets and the coating, causing the droplets to spherically roll off. When applied to the skirts of insulators, it effectively prevents droplets from forming a continuous water film on the skirt surface. Simultaneously, the extremely high thermal conductivity of the ceramic itself forms an effective heat-conducting network within the coating, rapidly melting surface ice. Combined with the superhydrophobicity, this reduces the adhesion of ice to the skirt surface, thus achieving self-cleaning and anti-icing coverage of the skirt. This is particularly suitable for power transmission lines in heavily polluted areas and regions with high fire safety requirements.
[0023] Furthermore, the hexagonal boron nitride powder added to the coating provides excellent interfacial bonding with the substrate and synergistically reduces the dielectric constant of the coating with the long-chain fluorinated hydrocarbon layer introduced from the nano-silica in the coating, thereby enhancing the coating's insulation performance. In humid and polluted environments, the coating prevents the formation of continuous water films, blocks leakage current paths, effectively prevents flashover accidents, ensures the electrical reliability of transmission lines, and significantly improves the flashover voltage of the material. On this basis, the chemical and thermal stability of the fluorocarbon chain resists corrosive gas erosion in harsh environments, ensuring that the insulation performance does not decline due to chemical corrosion. When applied to insulator skirts, in highly corrosive environments such as coastal salt spray, chemical industrial parks, and frequent acid rain, the skirt surface does not powder, peel, or produce conductive corrosion products, and its electrical and mechanical properties remain stable over a long period.
[0024] This invention adds nano-sized hexagonal boron nitride powder and silicon carbide to micron-sized hexagonal boron nitride powder. The nanoparticles fill the pores between the micron-sized particles, achieving a high filling density through tight bonding and effectively improving the flexural strength and fracture toughness of the ceramic. Simultaneously, the long-chain alkyl groups on the modified nano-silica provide steric hindrance, preventing particle agglomeration and improving the overall uniformity and performance stability of the coating. The long-chain alkyl groups also possess good flexibility and rotatability, absorbing and dissipating energy under external forces, making the coating less prone to cracking and peeling under impact or temperature changes. Furthermore, the long carbon chains act as a lubricant and internal toughening agent, significantly improving the coating's wear resistance and crack propagation resistance. When applied to insulator skirts, they effectively resist icing, wind vibration, and mechanical impacts during construction and installation, preventing skirt breakage and cracking. Detailed Implementation
[0025] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0026] Example 1 A method for preparing hexagonal boron nitride ceramics includes the following steps: Step 1: Take 60g of 1-2μm hexagonal boron nitride powder, 25g of 400nm hexagonal boron nitride powder, and 15g of 500nm silicon carbide powder. Treat each powder with a 5% (w / w) dilute hydrochloric acid solution to remove impurities. After washing and drying, mix the powder with 5g of boron oxide and place it in a ball mill jar. Add zirconium oxide grinding balls and anhydrous ethanol and ball mill for 20 hours. Then dry and sieve the ball-milled mixture. Place the resulting composite powder into a mold and sinter it in a spark plasma sintering furnace under a vacuum atmosphere. The sintering temperature is 1600℃, the sintering pressure is 40MPa, and the holding time is 10min. Then slowly depressurize and cool with the furnace. After the instrument cools to room temperature, take out the sample to obtain a hexagonal boron nitride ceramic block. Step 2: Take 3g of polydimethylsiloxane and 0.4g of 200nm hexagonal boron nitride powder, add them to a mixed solution of 20mL n-hexane and 40mL ethanol, sonicate the mixed solution for 10min, then add 1.6g of modified nano silica to the mixed solution, sonicate for 20min to obtain a modified coating, spray the modified coating onto the cleaned hexagonal boron nitride ceramic block, dry at room temperature for 20min after spraying, and then put it into an oven at 100℃ to dry for 2h to obtain hexagonal boron nitride ceramic; The preparation method of modified nano-silica includes the following steps: After activating 2g of nano-silica at 350℃ for 5h, it was added to the reactor along with 1g of modifier and 40mL of toluene. The mixture was ultrasonically dispersed at room temperature for 15min. The system temperature was then raised to 70℃ and reacted at this temperature for 10h. After the reaction was completed, the solid was filtered out. The obtained solid was then washed with anhydrous ethanol and dried to obtain modified nano-silica. The preparation method of the modifier includes the following steps: S1. Take 0.25g vanillinol and 0.6g 3-pentadecanylphenol into a reactor, add 10mL of anhydrous ethanol, and add dropwise a mixture of 0.5mL of 95% concentrated sulfuric acid and 1mL of anhydrous ethanol under an ice-water bath. After the addition is complete, heat to 25℃ and stir the reaction for 2h. After the reaction is complete, extract the product with ethyl acetate and retain the organic phase. Then wash the organic phase with saturated brine and dry to obtain a hydrophobic intermediate. S2. Take 0.5g of hydrophobic intermediate and 0.9g of cesium carbonate in a reactor, add 10mL of dimethyl sulfoxide under a nitrogen atmosphere, stir and react at 30℃ for 14h, then raise the temperature to 40℃, add 0.9g of 2-bromo-2-perfluoro-n-butylethylene dropwise to the mixed system, and react at a constant temperature for 24h after the addition is completed. After the reaction is completed, filter to remove the solid, distill the filtrate under reduced pressure, extract with ethyl acetate and retain the organic phase, wash the organic phase with saturated sodium chloride solution and deionized water respectively and dry to obtain the hydrophobic agent; S3. Take 0.9g of hydrophobic agent, 0.05g of lithium hydroxide, and 10mL of isopropanol into a reactor. Add 0.5g of silane coupling agent KH-550 under a nitrogen atmosphere. Stir the reaction at room temperature for 3h. After the reaction is completed, remove the solvent by rotary evaporation and then dry the product to obtain the modifier.
[0027] Example 2 A method for preparing hexagonal boron nitride ceramics includes the following steps: Step 1: Take 66g of 1-2μm hexagonal boron nitride powder, 29g of 200nm hexagonal boron nitride powder, and 5g of 400nm silicon carbide powder. Treat them with 15% dilute hydrochloric acid solution to remove impurities, and wash and dry them. Mix the powder with 6g of boron oxide and put it into a ball mill jar. Add zirconium oxide grinding balls and anhydrous ethanol, and ball mill for 24 hours. Then dry and sieve the ball-milled mixture. Put the obtained composite powder into a mold and sinter it in a spark plasma sintering furnace under vacuum atmosphere. The sintering temperature is 1600℃, the sintering pressure is 40MPa, and the holding time is 10min. Then slowly depressurize and cool with the furnace. After the instrument cools to room temperature, take out the sample to obtain hexagonal boron nitride ceramic block. Step 2: Take 5g of polydimethylsiloxane and 0.8g of 200nm hexagonal boron nitride powder, add them to a mixed solution of 30mL n-hexane and 60mL ethanol, sonicate the mixed solution for 20min, then add 2.4g of modified nano silica to the mixed solution, sonicate for 30min to obtain a modified coating, spray the modified coating onto the cleaned hexagonal boron nitride ceramic block, dry at room temperature for 30min after spraying, and then put it into an oven at 120℃ to dry for 3h to obtain hexagonal boron nitride ceramic; The preparation method of modified nano-silica includes the following steps: After activating 3g of nano-silica at 400℃ for 5h, it was added to the reactor along with 1.2g of modifier and 50mL of toluene. The mixture was ultrasonically dispersed at room temperature for 25min. The system temperature was then raised to 80℃ and reacted at this temperature for 8h. After the reaction was completed, the solid was filtered out and washed with anhydrous ethanol and dried to obtain modified nano-silica. The preparation method of the modifier includes the following steps: S1. Take 0.32g vanillinol and 1.0g 3-pentadecanylphenol into a reactor, add 12mL of anhydrous ethanol, and add dropwise a mixture of 0.6mL of 98% concentrated sulfuric acid and 1.2mL of anhydrous ethanol under an ice-water bath. After the addition is complete, heat to 30℃ and stir the reaction for 3h. After the reaction is complete, extract the product with ethyl acetate and retain the organic phase. Then wash the organic phase with saturated brine and dry to obtain a hydrophobic intermediate. S2. Take 0.7g of hydrophobic intermediate and 1.1g of cesium carbonate in a reactor, add 15mL of dimethyl sulfoxide under a nitrogen atmosphere, stir and react at 35℃ for 14h, then raise the temperature to 50℃, add 1.1g of 2-bromo-2-perfluoro-n-butylethylene dropwise to the mixture, and react at a constant temperature for 24h after the addition is completed. After the reaction is completed, filter to remove the solid, distill the filtrate under reduced pressure, extract with ethyl acetate and retain the organic phase, wash the organic phase with saturated sodium chloride solution and deionized water respectively and dry to obtain the hydrophobic agent; S3. Take 1.1g of hydrophobic agent, 0.06g of lithium hydroxide, and 15mL of isopropanol into a reactor. Add 0.6g of silane coupling agent KH-540 under a nitrogen atmosphere. Stir the reaction at room temperature for 4h. After the reaction is completed, remove the solvent by rotary evaporation and then dry the product to obtain the modifier.
[0028] Example 3 A method for preparing hexagonal boron nitride ceramics includes the following steps: Step 1: Take 63g of 1-2μm hexagonal boron nitride powder, 27g of 300nm hexagonal boron nitride powder, and 10g of 500nm silicon carbide powder. Treat them with 10% dilute hydrochloric acid solution to remove impurities, and wash and dry them. Mix the powder with 5.5g of boron oxide and put it into a ball mill jar. Add zirconium oxide grinding balls and anhydrous ethanol, and ball mill for 22h. Then dry and sieve the ball-milled mixture. Put the obtained composite powder into a mold and sinter it in a vacuum atmosphere using a spark plasma sintering furnace. The sintering temperature is 1600℃, the sintering pressure is 45MPa, and the holding time is 13min. Then slowly depressurize and cool with the furnace. After the instrument cools to room temperature, take out the sample to obtain hexagonal boron nitride ceramic block. Step 2: Take 4g of polydimethylsiloxane and 0.6g of 300nm hexagonal boron nitride powder, add them to a mixed solution of 25mL n-hexane and 50mL ethanol, sonicate the mixed solution for 15min, then add 2.0g of modified nano-silica to the mixed solution, sonicate for 25min to obtain a modified coating, spray the modified coating onto the cleaned hexagonal boron nitride ceramic block, dry at room temperature for 25min after spraying, and then place it in an oven at 110℃ to dry for 2.5h to obtain hexagonal boron nitride ceramic; The preparation method of modified nano-silica includes the following steps: After activating 2.5g of nano-silica at 350℃ for 6h, it was added to the reactor along with 1.1g of modifier and 45mL of toluene. The mixture was ultrasonically dispersed at room temperature for 20min. The system temperature was then raised to 75℃ and reacted at this temperature for 10h. After the reaction was completed, the solid was filtered out, and the obtained solid was washed with anhydrous ethanol and dried to obtain modified nano-silica. The preparation method of the modifier includes the following steps: S1. Take 0.28g vanillinol and 0.8g 3-pentadecanylphenol into a reactor, add 12mL of anhydrous ethanol, and add dropwise a mixture of 0.55mL of 96% concentrated sulfuric acid and 1.1mL of anhydrous ethanol under an ice-water bath. After the addition is complete, heat to 25℃ and stir the reaction for 2h. After the reaction is complete, extract the product with ethyl acetate and retain the organic phase. Then wash the organic phase with saturated brine and dry to obtain a hydrophobic intermediate. S2. Take 0.6 g of hydrophobic intermediate and 1.0 g of cesium carbonate in a reactor, add 15 mL of dimethyl sulfoxide under a nitrogen atmosphere, stir and react at 30 °C for 12 h, then raise the temperature to 45 °C, add 1.0 g of 2-bromo-2-perfluoro-n-butylethylene dropwise to the mixture, and react at a constant temperature for 22 h after the addition is completed. After the reaction is completed, filter to remove the solid, distill the filtrate under reduced pressure, extract with ethyl acetate and retain the organic phase, wash the organic phase with saturated sodium chloride solution and deionized water respectively and dry to obtain the hydrophobic agent; S3. Take 1.0g of hydrophobic agent, 0.055g of lithium hydroxide, and 15mL of isopropanol into a reactor. Add 0.55g of silane coupling agent KH-550 under a nitrogen atmosphere. Stir the reaction at room temperature for 3.5h. After the reaction is completed, remove the solvent by rotary evaporation and then dry the product to obtain the modifier.
[0029] Comparative Example 1 A method for preparing hexagonal boron nitride ceramics includes the following steps: Step 1: Take 63g of 1-2μm hexagonal boron nitride powder, 27g of 300nm hexagonal boron nitride powder, and 10g of 500nm silicon carbide powder. Treat them with 10% dilute hydrochloric acid solution to remove impurities, and wash and dry them. Mix the powder with 5.5g of boron oxide and put it into a ball mill jar. Add zirconium oxide grinding balls and anhydrous ethanol, and ball mill for 22h. Then dry and sieve the ball-milled mixture. Put the obtained composite powder into a mold and sinter it in a vacuum atmosphere using a spark plasma sintering furnace. The sintering temperature is 1600℃, the sintering pressure is 45MPa, and the holding time is 13min. Then slowly depressurize and cool with the furnace. After the instrument cools to room temperature, take out the sample to obtain hexagonal boron nitride ceramic block. Step 2: Take 4g of polydimethylsiloxane and 0.6g of 300nm hexagonal boron nitride powder, add them to a mixed solution of 25mL n-hexane and 50mL ethanol, sonicate the mixed solution for 15min, then add 2.0g of nano-silica to the mixed solution, sonicate for 25min to obtain a coating, spray the coating onto the cleaned hexagonal boron nitride ceramic block, dry at room temperature for 25min after spraying, and then place it in an oven at 110℃ to dry for 2.5h to obtain hexagonal boron nitride ceramic.
[0030] Comparative Example 2 A method for preparing hexagonal boron nitride ceramics includes the following steps: Take 63g of 1-2μm hexagonal boron nitride powder, 27g of 300nm hexagonal boron nitride powder, and 10g of 500nm silicon carbide powder. Treat each powder with a 10% (w / w) dilute hydrochloric acid solution to remove impurities, and wash and dry them. Mix the powder with 5.5g of boron oxide and place it in a ball mill jar. Add zirconium oxide grinding balls and anhydrous ethanol, and ball mill for 22 hours. Then dry and sieve the ball-milled mixture. Place the resulting composite powder in a mold and sinter it in a spark plasma sintering furnace under a vacuum atmosphere. The sintering temperature is 1600℃, the sintering pressure is 45MPa, and the holding time is 13min. Then slowly depressurize and cool with the furnace. After the instrument cools to room temperature, take out the sample to obtain hexagonal boron nitride ceramic.
[0031] Comparative Example 3 A method for preparing hexagonal boron nitride ceramics includes the following steps: 63g of 1-2μm hexagonal boron nitride powder was treated with a 10% (w / w) dilute hydrochloric acid solution to remove impurities. After washing and drying, the powder was mixed with 3g of boron oxide and placed in a ball mill jar. Zirconia grinding balls and anhydrous ethanol were added, and the mixture was ball-milled for 22 hours. The ball-milled mixture was then dried and sieved. The resulting composite powder was placed in a mold and sintered in a spark plasma sintering furnace under a vacuum atmosphere at a temperature of 1600℃, a sintering pressure of 45MPa, and a holding time of 13min. The pressure was then slowly released, and the furnace was cooled. After the instrument cooled to room temperature, the sample was removed to obtain hexagonal boron nitride ceramic.
[0032] Performance testing The performance of the hexagonal boron nitride ceramics in Examples 1-3 and Comparative Examples 1-3 was tested: Hydrophobicity and electrical insulation tests: The surface water contact angle of each group of hexagonal boron nitride ceramics was tested according to GB / T 30447-2013, the flashover voltage of each group of hexagonal boron nitride ceramics was tested according to GB / T 16927.1-2011 and GB / T 775.2-2022, and the pollution flashover voltage of each group of hexagonal boron nitride ceramics was tested according to GB / T 4585-2004. The obtained hydrophobicity and electrical insulation monitoring data are shown in Table 1.
[0033] Table 1: Statistical Table of Monitoring Data on Hydrophobicity and Electrical Insulation
[0034] As can be seen from Table 1, compared with Comparative Examples 1-3, Examples 1-3 have larger surface water contact angles, flashover voltages, and pollution flashover voltages, indicating that applying a modified coating to hexagonal boron nitride ceramics can effectively improve the hydrophobicity and electrical insulation of the modified ceramics.
[0035] Relative density and mechanical property testing: The relative density of each group of hexagonal boron nitride ceramics was tested according to GB / T 25995-2010, the flexural strength and compressive strength of each group of hexagonal boron nitride ceramics were tested according to GB / T 6569-2006, and the mass loss of each group of hexagonal boron nitride ceramics was tested under the conditions of CS-10 grinding wheel, 1000g load and 1000 revolutions according to GB / T1768-2006. The relative density and mechanical property monitoring data obtained are shown in Table 2.
[0036] Table 2: Statistical Table of Relative Density and Mechanical Properties Monitoring Data
[0037] As can be seen from Table 2, compared with Comparative Example 3, Examples 1-3 have higher relative density, flexural strength, compressive strength and lower mass loss, indicating that applying a modified coating to hexagonal boron nitride ceramics can effectively improve the relative density and mechanical properties of the modified ceramics.
[0038] Corrosion resistance test: Refer to GB / T 1771-2007 to observe the appearance changes of the hexagonal boron nitride ceramics in Examples 1-3 and Comparative Example 1 after a salt spray test with 5% sodium chloride solution for 240 hours. The obtained corrosion resistance monitoring data are shown in Table 3.
[0039] Table 3: Statistical Table of Corrosion Resistance Monitoring Data
[0040] As can be seen from Table 3, there were no significant changes in the surfaces of Examples 1-3 after corrosion tests, while Comparative Example 1 showed obvious bubbling. Therefore, modifying the coating can effectively improve the corrosion resistance of hexagonal boron nitride ceramics.
[0041] The foregoing has provided a detailed description of one embodiment of the present invention, but this description is merely a preferred embodiment and should not be construed as limiting the scope of the invention. All equivalent variations and modifications made within the scope of the claims of this invention should still fall within the patent coverage of this invention.
Claims
1. A method for preparing hexagonal boron nitride ceramic, characterized in that, Includes the following steps: Step 1: Take 1-2μm hexagonal boron nitride powder, 200-400nm hexagonal boron nitride powder, and 200-500nm silicon carbide powder. Treat them with 5-15% dilute hydrochloric acid solution to remove impurities, and wash and dry them. Mix the powder with boron oxide and put it into a ball mill jar. Add zirconium oxide grinding balls and anhydrous ethanol, and ball mill for 20-24 hours. Then dry and sieve the ball-milled mixture. Put the obtained composite powder into a mold and sinter it in a vacuum atmosphere using a spark plasma sintering furnace. Then slowly depressurize and cool with the furnace. After the instrument cools to room temperature, take out the sample to obtain hexagonal boron nitride ceramic block. Step 2: Take polydimethylsiloxane and 200-400nm hexagonal boron nitride powder, add them to a mixed solution of n-hexane and ethanol, sonicate the mixed solution for 10-20 minutes, then add modified nano-silica to the mixed solution, sonicate for 20-30 minutes to obtain a modified coating, spray the modified coating onto the cleaned hexagonal boron nitride ceramic block, dry at room temperature for 20-30 minutes after spraying, and then put it into an oven at 100-120℃ to dry for 2-3 hours to obtain hexagonal boron nitride ceramic; The modified nano-silica is prepared by surface modification of nano-silica using a modifier. The modifier is prepared by alkylation coupling of vanillin and 3-pentadecanylphenol to obtain a hydrophobic intermediate, followed by ether synthesis reaction of the hydrophobic intermediate with 2-bromo-2-perfluoro-n-butylethylene to obtain a hydrophobic agent, and finally by Michael addition reaction of the hydrophobic agent with a silane coupling agent.
2. The method for preparing hexagonal boron nitride ceramic according to claim 1, characterized in that, In the first step, the mass ratio of 1-2μm hexagonal boron nitride powder, 200-400nm hexagonal boron nitride powder, 200-500nm silicon carbide powder, and boron oxide is 60-66:25-29:5-15:5-6. The sintering temperature is 1500-1700℃, the sintering pressure is 40-50MPa, and the holding time is 10-15min.
3. The method for preparing hexagonal boron nitride ceramic according to claim 1, characterized in that, In the second step, the mass ratio of polydimethylsiloxane, 200-400nm hexagonal boron nitride powder, and modified nano-silica is 3-5:0.4-0.8:1.6-2.4, and the volume ratio of n-hexane to ethanol in the mixed solution of n-hexane and ethanol is 1:
2.
4. The method for preparing hexagonal boron nitride ceramic according to claim 1, characterized in that, The preparation method of modified nano-silica includes the following steps: After activating nano-silica at 350-400℃ for 5-7h, it is added to the reactor along with a modifier and toluene. The mixture is then ultrasonically dispersed at room temperature for 15-25min. The system temperature is then raised to 70-80℃ and reacted at this temperature for 8-12h. After the reaction is complete, the solid is filtered out, washed with anhydrous ethanol, and dried to obtain modified nano-silica.
5. The method for preparing hexagonal boron nitride ceramic according to claim 4, characterized in that, The mass ratio of the nano-silica to the modifier is 2-3:1-1.
2.
6. The method for preparing hexagonal boron nitride ceramic according to claim 4, characterized in that, The preparation method of the modifier includes the following steps: S1. Vanillin and 3-pentadecanylphenol were placed in a reactor, and anhydrous ethanol was added. A mixture of concentrated sulfuric acid and anhydrous ethanol was added dropwise under an ice-water bath. After the addition was complete, the temperature was raised to 25-30℃ and the reaction was stirred for 1-3 hours. After the reaction was completed, the product was extracted with ethyl acetate and the organic phase was retained. The organic phase was then washed with saturated brine and dried to obtain a hydrophobic intermediate. S2. Take the hydrophobic intermediate and cesium carbonate in a reactor, add dimethyl sulfoxide under a nitrogen atmosphere, stir the reaction at 30-35℃ for 10-14h, then raise the temperature to 40-50℃, add 2-bromo-2-perfluoro-n-butylethylene dropwise to the mixed system, and after the dropwise addition is completed, react at a constant temperature for 20-24h. After the reaction is completed, filter to remove the solid, distill the filtrate under reduced pressure, extract with ethyl acetate and retain the organic phase, wash the organic phase with saturated sodium chloride solution and deionized water respectively and dry to obtain the hydrophobic agent; S3. Take the hydrophobic agent, lithium hydroxide, and isopropanol into a reactor, add the silane coupling agent under a nitrogen atmosphere, stir the reaction at room temperature for 3-4 hours, remove the solvent by rotary evaporation after the reaction is completed, and then dry the product to obtain the modifier.
7. The method for preparing hexagonal boron nitride ceramic according to claim 6, characterized in that, In step S1, the mass ratio of vanillin to 3-pentadecanylphenol is 0.25-0.32:0.6-1, and the volume ratio of concentrated sulfuric acid to anhydrous ethanol in the mixture of concentrated sulfuric acid and anhydrous ethanol is 0.5-0.6:1-1.2, wherein the mass fraction of concentrated sulfuric acid is 95-98%. In step S2, the mass ratio of hydrophobic intermediate, cesium carbonate, and 2-bromo-2-perfluoro-n-butylethylene is 0.5-0.7:0.9-1.1:0.9-1.
1. In step S3, the mass ratio of hydrophobic agent, lithium hydroxide, and silane coupling agent is 0.9-1.1:0.05-0.06:0.5-0.6, and the silane coupling agent is silane coupling agent KH-550 or silane coupling agent KH-540.
8. A hexagonal boron nitride ceramic, characterized in that, It is prepared by the preparation method described in any one of claims 1-7.
9. The application of the hexagonal boron nitride ceramic according to claim 8 in power and energy systems, characterized in that, The hexagonal boron nitride ceramic is used in the insulator skirt of high-voltage transmission lines.
10. The application of the hexagonal boron nitride ceramic according to claim 9, characterized in that, In application, the second step of the preparation method of the hexagonal boron nitride ceramic is formed using an umbrella skirt mold, followed by subsequent spraying to obtain a hexagonal boron nitride ceramic umbrella skirt. This skirt is then assembled with the insulator core rod and fittings using adhesive or mechanical clamping to form a complete insulator for use in transmission lines.